Cześć!
POZIOM A
[tex]2\cdot2^2\cdot2^5=2^{1+2+5}=2^8\\\\5^8:5^6=5^{8-6}=5^2\\\\(\frac{1}{3})^4\cdot(\frac{1}{3})^2\cdot(\frac{1}{3})^0=(\frac{1}{3})^{4+2+0}=(\frac{1}{3})^6[/tex]
POZIOM B
[tex]3^7:3^2:3^5=3^{7-2-5}=3^0\\\\0,2^4\cdot0,2^3:0,2^2=0,2^{4+3-2}=0,2^5\\\\(-\frac{1}{4})^5\cdot(-\frac{1}{4})^4:(-\frac{1}{4})^2=(-\frac{1}{4})^{5+4-2}=(-\frac{1}{4})^7[/tex]
POZIOM C
[tex](5^2)^2=5^{2\cdot2}=5^4=5\cdot5\cdot5\cdot5=625\\\\((\frac{2}{3})^5)^0=(\frac{2}{3})^{5\cdot0}=(\frac{2}{3})^0=1\\\\((-1)^{10})^{30}=(-1)^{10\cdot30}=(-1)^{300}=1[/tex]
POZIOM D
[tex](7^{12}:7^2\cdot7^2):(7^2\cdot7^{3})=7^{12-2+2}:7^{2+3}=\\\\=7^{12}:7^5=7^{12-5}=7^7[/tex]